The Prohibition of Sleeping After Dawn (A Study of Living Hadith in the Community of Batu Pennai Village, Daleman District, Bangkalan) - Sama’un, Sama’un; Imron, Moh; Xin, Derr; Martin, Weng (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2021)
The subject matter of this research is how the hadiths about the prohibition of sleeping after dawn that have lived traditions in the oral community of Batu Pennai village (a study of living sunnah in Batu Pennai village in Daleman sub-district Galis district Bangkalan)? The problems that will be solved in this study are: 1) How is the description of the hadith about sleeping after dawn 2) How is the form of hadith that has been traditionalized in Batu Pennai village, Daleman village, Galis sub-district, Bangkalan regency in daily life and 3) How is the practice of the hadith about the prohibition of sleeping after dawn in Batu Pennai village in Daleman village, Galis District, Bangkalan Regency. Living sunnah in this study is an oral living sunnah. The people of Batu Pennai village have an oral expression, which is actually a hadith. However, they express with different editorials with the same intention as what is conveyed by the Prophet's hadith. For example,